Oral health effects on the nutritional status of elderly people - Pavlović Jelena; Ivković Nedeljka; Račić Maja (Serbian Medical Society - Dental Section, Belgrade, 2019)
Introduction The aim of the study was to establish the association between oral health and malnutrition in people over the age of 65. Material and Methods Cross-sectional study included 146 respondents residing in gerontology center, and 300 respondents who lived in their own homes or with their families. Nutritional status was evaluated using the Mini Nutritive Scale and standardized questionnaire. Dental status was evaluated by clinical examination using inspection method. The presence and absence of teeth was evaluated in each dental arch (third molars were not taken into consideration). Also, the presence of prosthetic restorations (total and partial dentures) was noticed without analyzing their adequacy and functionality. Self-assessment of health with categorical components assessed the overall health status. The research was conducted in 2018. Results Most of respondents who had malnutrition or were at risk of malnutrition had worse dental status; they were completely or partially edentulous. There was high statistically significant difference in dental status of the upper (χ 2 =47,797; p < 0,001) and lower jaw (χ 2 = 66,680; p < 0,001). The number of lost teeth had an impact on self-assessment of general health (χ 2 = 47,270; p < 0,001). Conclusion Oral health status in elderly people had significant influence on nutritional status.